The viability of implementing hydrogen in the Commonwealth of Massachusetts - Hammerstrom, Brian; Niezrecki, Christopher; Hellman, Kelly; Jin, Xinfang; Ross, Michael B.; Mack, J. Hunter; Agar, Ertan; Trelles, Juan Pablo; Liu, Fuqiang; Che, Fanglin; Ryan, David; Narasimhadevara, Madhava S.; et al. (Frontiers in Energy Research, 2022)
In recent years, there has been an increased interest in hydrogen energy due to a desire to reduce greenhouse gas emissions by utilizing hydrogen for numerous applications. Some countries (e.g., Japan, Iceland, and parts of Europe) have made great strides in the advancement of hydrogen generation and utilization. However, in the United States, there remains significant reservation and public uncertainty on the use and integration of hydrogen into the energy ecosystem. Massachusetts, similar to many other states and small countries, faces technical, infrastructure, policy, safety, and acceptance challenges with regards to hydrogen production and utilization. A hydrogen economy has the potential to provide economic benefits, a reduction in greenhouse gas emissions, and sector coupling to provide a resilient energy grid. In this paper, the issues associated with integrating hydrogen into Massachusetts and other similar states or regions are studied to determine which hydrogen applications have the most potential, understand the technical and integration challenges, and identify how a hydrogen energy economy may be beneficial. Additionally, hydrogen’s safety concerns and possible contribution to greenhouse gas emissions are also reviewed. Ultimately, a set of eight recommendations is made to guide the Commonwealth’s consideration of hydrogen as a key component of its policies on carbon emissions and energy.